KONVERGENSI MAKNA KATA BERSINONIM DALAM AL QUR’AN - Mukhlas, Moh. Mukhlas (IAIN Ponorogo, 2016)
Abstract: Qur'an is a miracle that has a deep meaning and none can replace those structures, removing or adding words, because each word has a miracle. In Qur'an, there is an interesting phenomenon such meaning convergent that associated with synonymous in context. The aims of this study are to describe and explain the significance of convergence in Qur'an especially synonymous words. Hermeneutic and content analysis were used to analysis those phenomenon. It can be found that convergence of meaning to synonymous words in the Qur'an does not have similar semantic features or same meaning, but there is a shift, changing the meaning, contradictory and meaning resistance. Then the terms of shifts and changing the meaning are as follow (a) the synonymous words that have antonyms meaningful, (b) the synonymous words that have meaningful process, (c) the synonymous words that have depth meaning, and (d) the synonymous words that have deductive-inductive meaning.Keywords: meaning convergent, contextual meaning